Patient perceived changes in sexual dysfunction after initiation of natalizumab for multiple sclerosis. Issue 2 (June 2018) - Robertson, Derrick; Aungst, Angela; Collier, Ryan; Vivar, Jhulianna; Moreo, Natalie; Casady, Lise; Vu, Tuan
Purpose: Sexual dysfunction is a common but often overlooked secondary symptom of multiple sclerosis (MS) and can be associated with a decreased health-related quality of life (HRQoL). Natalizumab is a disease-modifying therapy approved for the treatment of relapsing forms of MS. In addition to its efficacy, those using natalizumab have shown improvement in HRQoL parameters, including fatigue and cognition. The idea that improvement in fatigue may also correlate with improvement in sexual dysfunction is the impetus for this study. Methods: A single-center, open-label, single-arm, 24-week study was performed to evaluate perceived change in sexual dysfunction in MS patients treated with natalizumab. Adults with relapsing MS initiating natalizumab treatment and had a baseline level of sexual dysfunction were enrolled. The primary endpoint was change in the MS Intimacy and Sexuality Questionnaire-19 (MSISQ-19) score from baseline to week 24. Mean age of patients was 41 years, median disease duration was 7 years, and 73% of patients used at least one prior MS disease-modifying therapy. Results: Natalizumab-treated patients experienced improvement in sexual dysfunction within the first 24 weeks of starting therapy, as demonstrated by the primary subscale of the MSISQ-19 questionnaire (–0.6976, p = 0.02). Conclusions: Given the high prevalence of sexual dysfunction in MS patients and the significant impact it has on HRQoL, more research on this often overlooked symptom of MS could be very informative for patients that are deciding to initiate a new disease modifying therapy.